Study of shelf life of beef treated with union - Mohd Zharif Ramli (2013)
Fresh beef is highly perishable due to its biological composition but it is preferable in the market by the consumers. The shelf life of the fresh beef is about 1-2 days in commercial refrigerator 4°C and extension of shelf life is needed to avoid losses. The effects of two variety of onion Alliurn cepa L.(Yellow onion and Red Onion) on the microbiological and changes of pH on ground beef patties were evaluated by counted the viable bacteria in cfu and pH meter respectively. Ground beef were incorporated with extract and ground onions respectively in Test 1 and 2. All samples were kept at 4°C for 10 d. Addition of extract and ground onions preserved the ground beef until day 7 and day 3 respectively in refrigerated temperature. Red onion can be preservative agents better than yellow onion. Overall, the results of this study indicate that the addition of onion extracts reduced the microbial quality and extended the shelf life of fresh ground beef compared to incorporation of ground onions.